'Charting a new course for prostate cancer' – currying favor for docetaxel in hormone-sensitive metastatic prostate cancer. Issue 11 (November 2014) - Voskoboynik, Mark; Staffurth, John; Malik, Zafar; Sweeney, Christopher; Chowdhury, Simon
<x xml:space="preserve">Abstract</x> Docetaxel has an established role in the treatment of metastatic castrate-resistant prostate cancer. A number of recent treatments have been shown to improve the survival outcomes for this group of patients and many with improved toxicity profiles, bringing the role of docetaxel into question. We discuss the results and implications of the CHAARTED study that demonstrated a significant improvement in overall survival with docetaxel in metastatic hormone-sensitive prostate cancer.